Pengaruh Anonimitas di Media Sosial terhadap Kebebasan Berpendapat dan Tanggung Jawab Hukum Studi Kasus: (Analisis Kasus Akun Fufufafa dalam Penyebaran Informasi Palsu dan Ujaran Kebencian di Media Sosial Twitter) : Penelitian - Simamora, Rani Marsela; Siahaan, Parlaungan Gabriel; Novridah Reanti Purba; Jane Agustin Sianturi; Ananda Meriah Ate Banurea; Sabar Saur Matua Br Limbong; Asya Junita Rajagukguk; Tasya Maulita (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Anonymity comes from the Greek word 'anonymia' which means 'without a name' which means unknown identity information, which can be used to identify objects in the form of humans or objects. This study examines the effect of anonymity on social media on freedom of speech and legal responsibility, with a case study of the